2013
DOI: 10.1002/ceat.201200486
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Modeling of Gas‐Liquid Two‐Phase Flow around a Spherical Particle

Abstract: Microscale studies, which can provide basic information for meso-and macroscale studies, are essential for the realization of flow characteristics of a packed bed. In the present study, the effects of gas velocity, liquid velocity, liquid-solid contact angle, and liquid viscosity on the flow behavior were parametrically investigated for gas-liquid two-phase flow around a spherical particle, using computational fluid dynamics (CFD) methodology in combination with the volume-offluid (VOF) model. The VOF model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…On the contrary, for higher viscosity liquid, film flow appears in most regions of the bed, and the liquid surface coverage on each particle increases. The results are consistent with our previous work (Du et al, 2013) that when liquids flow around a spherical particle, the liquid film thickness becomes thinner for high viscosity liquids but the flow time of this liquid becomes longer. It can be seen that although a better liquid distribution can be obtained inside the packed bed, the liquid coverage on the particle surfaces may be reduced by lowering the liquid viscosity.…”
Section: Influence Of Liquid Viscositysupporting
confidence: 94%
See 4 more Smart Citations
“…On the contrary, for higher viscosity liquid, film flow appears in most regions of the bed, and the liquid surface coverage on each particle increases. The results are consistent with our previous work (Du et al, 2013) that when liquids flow around a spherical particle, the liquid film thickness becomes thinner for high viscosity liquids but the flow time of this liquid becomes longer. It can be seen that although a better liquid distribution can be obtained inside the packed bed, the liquid coverage on the particle surfaces may be reduced by lowering the liquid viscosity.…”
Section: Influence Of Liquid Viscositysupporting
confidence: 94%
“…A contact angle of 90 • or greater generally characterizes a surface as nonwettable (hydrophobic), while an angle less than 90 • means that the surface is wettable (hydrophilic). Du et al (2013) observed that the contact angle showed a significant impact on the flow behavior of gas-liquid flow around a spherical particle. Therefore, a similar effect of the contact angle on the flow behavior in a packed bed is expected.…”
Section: Influence Of Contact Anglementioning
confidence: 97%
See 3 more Smart Citations